BUDDHIST DISCOURSES AND MOVEMENTS IN OVERCOMING THE REGENERATION CRISIS (Journal of Pharmaceutical Negative Results, 2023)
The regeneration crisis among Buddhists is a threat to the existence of Buddhists. This study aims to describe the discourses and movements of Buddhists in overcoming the crisis regeneration. This study reveals the causes of the regeneration crisis, the discourse's that were builts to overcome the regeneration crisis, and the movements carried out to overcome the Buddhist regeneration crisis. The research was conduct in Jepara, Central Java. The research method uses a holistic descriptive approach. The results of the studies stated that one of the causes of the regeneration crisis was religious conversion during the marriage, the discourse built by Buddhists through a shared space as a matchmaking agency, and the movement through the establishment of the Jepara Buddhist Youth Association (PMMBJ). This institution was used as a space for young Buddhists to get to know each other interpersonally and the media to find a mate and build a happy family through marriage. Through the discourses and movements, it is possible to minimize religious conversion.